Development of Regulations and Problems in the Conversion of Agricultural/Paddy Land Functions and Their Resolving With Land Incompatibility in Indonesia - Hendry Chandra; F. H. Ridwan (Universitas Muhammadiyah Sumatera Utara, 2023)
The spatial plans that have been made so far have not prioritized paddy or agricultural land; this is reflected in the fact that the regional governments have not issued any spatial plans related to paddy or agricultural land. Recently, real threats have occurred because the transfer of agricultural land or rice fields has been the subject of discussion at the level of environmental experts or by the central government through the relevant ministries. Whereas the conversion of agricultural land and rice fields in the last two to three years has become a priority of the Central Government with the issuance of legal products from presidential regulations to the relevant ministries, The determination of a map of paddy fields protected by the Ministry of Agrarian Affairs and Spatial Planning Head on December 16, 2021, is a positive thing for policy makers at the local government level and should be used as a basis for giving approval or rejection of requests for land conversion changes in the future. Regarding the discrepancy (overlapping) of protected paddy fields against the existing spatial plan (RTR).